2010
DOI: 10.1002/j.2161-1920.2010.tb00095.x
|View full text |Cite
|
Sign up to set email alerts
|

the 2007 california citrus freeze: vulnerability, poverty, and unemployment issues of farmworkers

Abstract: In January of 2007, freezing temperatures destroyed citrus and vegetable crops in California. By May 2007, more than 9,000 freeze‐related unemployment applications had been filed. Through face‐to‐face interviews, this study documents the experience of 63 farmworkers to find out how they survived the freeze and accessed services. Findings revealed that more than half of the interviewees did not seek benefits from the governmental One‐Stop centers set up to help them. Less than 10% of interviewees stated the ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…A review of the vocational psychology literature between 1990 and 2010 revealed 35 articles on U.S. immigrants across four career journals (Flores, Hsieh, & Chiao, 2011). Among these, two empirical studies were on adult Latino immigrants (Orozco, 2010; Shinnar, 2007). Data-driven psychological studies that provide an in-depth understanding of Latino immigrants' experiences with work in the United States are essential for career interventions and the development of theories related to immigrants' career development.…”
mentioning
confidence: 99%
“…A review of the vocational psychology literature between 1990 and 2010 revealed 35 articles on U.S. immigrants across four career journals (Flores, Hsieh, & Chiao, 2011). Among these, two empirical studies were on adult Latino immigrants (Orozco, 2010; Shinnar, 2007). Data-driven psychological studies that provide an in-depth understanding of Latino immigrants' experiences with work in the United States are essential for career interventions and the development of theories related to immigrants' career development.…”
mentioning
confidence: 99%